Store Atmosphere and Store Location as Determinants of Consumer Buying Interest - Kurniawati Mulyanti; Mutdi Ismuni; Rustomo Rustomo (Kontigensi : Jurnal Ilmiah Manajemen, 2022)
The purpose of this study was to analyze the influence of the store atmosphere and store location on consumer buying interest in the Alfamidi Dukuh Zamrud. This study uses two independent variables, namely the atmosphere of the store and the location of the store with one dependent variable, namely consumer buying interest. The method of this research is to use a descriptive quantitative method, the sample in this study is consumers who have purchased goods from Alfamidi Dukuh Zamrud and taken a sample of 100 respondents. Based on the questionnaire answers that have been processed by SPSS, the statistical calculation results obtained a coefficient number of store atmosphere and store location has a significant effect of 63.9% on consumer buying interest, while the remaining 36.1% is influenced by other factors that are not researched in this study.